Methods for Predicting Stock Indexes (2013)
This paper presents a literature review on methods that have been used in the last two decades to predict Stock Market Indexes -- Methods studied range from those enabling to grab the linear characteristics present in the stock market indexes, going through those that focus on non-linear features and finally hybrid methods that are more robust, since they capture linear and non-linear features -- In addition, this research includes methods that use macroeconomic variables to predict indexes from different stock exchanges around the world